A pilot randomized controlled study of integrated kidney palliative care and chronic kidney disease care implemented in a safety-net hospital: Protocol for a pilot study of feasibility of a randomized controlled trial - Jennifer S. Scherer; Wenbo Wu; Chen Lyu; Keith S. Goldfeld; Abraham A. Brody; Joshua Chodosh; David Charytan (Contemporary Clinical Trials Communications, 2025)
Background: Chronic kidney disease (CKD) impacts more than 800 million people. It causes significant suffering and disproportionately impacts marginalized populations in the United States. Kidney palliative care has the potential to alleviate this distress, but has not been tested. This pilot study evaluates the feasibility of a randomized clinical trial (RCT) testing the efficacy of integrated kidney palliative and CKD care in an urban safety-net hospital. Methods: This is a single-site pilot RCT designed to enroll 85 participants, with a goal of at least 60 completing the study. The inclusion criteria are adults 18 or older, who are either Spanish or English speakers, have an estimated Glomerular Filtration Rate (eGFR) of ≤30 mL/min/1.73 m2, and are receiving care at our safety net hospital. Participants will be randomized in permuted blocks of two or four to either the intervention group, who will receive monthly ambulatory care visits for six months with a palliative care provider trained in kidney palliative care, or to usual nephrology care. Primary outcomes are feasibility of recruitment, retention, fidelity to the study visit protocol, and the ability to collect outcome data. These outcomes include symptom burden, quality of life, and engagement in advance care planning. Discussion: This pilot RCT will provide essential data on the feasibility of testing integrated palliative care in CKD care in an underserved setting. These outcomes will inform a larger, fully powered trial that tests the efficacy of our kidney palliative care approach. Clinical trial registration: NCT04998110.